Analisis Potensi Bahaya pada Stasiun Sterilizer di PTPN IV PKS Tanjung Seumantoh Menggunakan Metode Job Safety Analysis (JSA) - Dewiyana; Ryan Pramanda; Nurmalawati; Hanna Amani Fadilah Saragih (Universitas Katolik Darma Cendika, 2024)
This study aims to identify potential hazards at the sterilizer station in PTPN IV using the Job Safety Analysis (JSA) method. This method is applied to identify potential hazards in each work process at the sterilizer station. The analysis results show that the highest hazard potential occurs in two processes: during the sterilization of Fresh Fruit Bunches (FFB) with a risk score of 5, and when opening the sterilizer door after sterilization is complete, with a risk score of 15. These two processes require further control measures. Additionally, analysis was carried out on six other processes, including floor cleaning in the sterilizer area, pulling the cart using a capstan, adding and releasing steam at peak 1, peak 2, and peak 3 during sterilization, and attaching the capstan rope to the hook at the end of the cart. Therefore, optimal control efforts are needed during the FFB sterilization process and the opening of the sterilizer door to minimize hazard risks to a low level.